Laparoscopic management of ureter stones, comparison of two techniques (Annals of Medical Research, 2021)
Aim: With the improvement of minimally invasive urology procedures, open surgical interventions are less common to treat ureteralcalculus. Laparoscopic ureterolithotomy (LU) indications are large multiple and/or impacted ureteral calculus that may not be treatedwith shock-wave lithotripsy or ureterorenoscopy approaches. In this study, we aimed to compare laparoscopic retroperitoneal andtransperitoneal ureterolithotomy techniques in terms of perioperative-postoperative results.Materials and Methods: We reviewed 45 patients with large and impacted upper ureter calculus who underwent transperitonealor retroperitoneal LU between January 2012 and December 2017. The transperitoneal and retroperitoneal routes were grouped asgroup 1 and 2, respectively. Groups were crosschecked according to preoperative, intraoperative, and postoperative clinical datum.Results: We did not find statistically meaningful disparity between groups with regards to age, gender, stone size, blood loss andbody mass index. The stone free accomplishment ratio was 100% in group 1 and 2. Visual analogue scale scores were higher andstatistically meaningful in group 1 (p